Predictors of angiographic restenosis in patients with coronary artery disease who have undergone percutaneous coronary intervention with drug eluting stents - Praveen, S.; R., Baiju; Radhakrishnan, V. V.; K. K., Sarosh Kumar (International Journal of Research in Medical Sciences, 2018)
Background: Percutaneous transluminal coronary angioplasty (PTCA) is now widely accepted as a nonsurgical revascularization procedure for selected patients with CAD. In-stent restenosis (ISR) is a frequent complication after PCI which limits its long-term efficacy. Identification of those clinical and angiographic characteristics that may predict the risk of restenosis is extremely important to eliminate restenosis. In this context we conducted this study to assess the profile of patients with drug eluting stents - ISR with an emphasis on demographic characteristics, risk factors, mode of presentation and coronary angiographic characterization. Methods: This study was a Case control study based on the catheterization registry of all patients who have undergone PCI with DES during the period from October 2012 to April 2015. All patients who have undergone PCI with DES and repeat coronary angiogram for evaluation of symptoms and detected to have ISR during same period were taken as case and age matched patients who had previously undergone PCI with DES and repeat coronary angiogram for evaluation of symptoms between 1/10/2012 to 30/4/2015 and detected to have fully patent stents were taken as control. Results: A total of 26 patients were detected to have ISR during the study period as per the study protocol with equal number of age matched controls. The most common presentation of ISR was as chronic stable angina (70%). Binary logistic regression analysis of 6 factors namely diabetes, hypertension, lesion type, stent diameter, stent length and stent overlap found significant in univariate analysis, showed only the lesion type to be statistically significant with p value of 0.023. Conclusions: Patients who have undergone PCI with DES particularly for complex lesions, diabetics with longer stents, lesser diameter stents and overlapping stents need to be meticulously followed up to rule out the possibility of restenosis, as in a small number of patients the presentation could be ACS with comparatively bad prognosis.